BDNF-TrkB signaling maintains alveolar epithelial type 2 cell survival and is blocked in hyperoxia-induced neonatal lung injury - Kuiper-Makris, Celien; Fahle, Luise; Zeitouny, Caroline; Vohlen, Christina; Klymenko, Oleksiy; Stephan, Stephanie; Mižíková, Ivana; Bae-Gartz, Inga; Selle, Jaco; Hirani, Dharmesh; Belu, Andreea; Hucho, Tim; et al. (American journal of respiratory cell and molecular biology, 2025)
Oxygen supplementation causes an arrest of alveolar formation and a depletion of alveolar epithelial type 2 (AT2) cells in preterm infants, both characteristics of bronchopulmonary dysplasia. BDNF (brain-derived neurotrophic factor) is a key integrator of cell homeostasis and contributes to chronic lung diseases. In this study, 1) wild-type mice were exposed to 85% O2 or 21% O2 from birth to postnatal day (P)28, followed by spatiotemporal profiling of pulmonary BDNF signaling on P3-P70; and 2) lung epithelial cells (MLE12), primary murine AT2, and precision-cut lung slices were treated with nonselective Trk inhibitor (K252a), selective TrkB antagonist (Ana12), and TrkB agonist (7,8-dihydroxyflavone). Single-cell transcriptomic profiling revealed an expression of Bdnf in mesenchymal cells but no changes during postnatal development. In contrast, immunofluorescent staining showed a predominant localization of TrkB in AT2 and ACTA2+ cells; its expression and phosphorylation were increased at P7-P21. Although hyperoxia induced a 40-fold upregulation of lung Bdnf and a 3-fold elevation of serum BDNF, TrkB abundance and activation decreased by 90%. This was related to a lower Sftpc and increased Acta2 in lungs. Blockade of Trk(B) reduced survival of MLE12 and murine AT2 with a loss of epithelial AT1 and AT2 markers, whereas the TrkB agonist increased survival and regulated AT2 maintenance in precision-cut lung slices after hyperoxia. Our data identified an important functional role of TrkB signaling in AT2 cells, a mechanism that is blocked in neonatal mouse lungs after hyperoxia and may contribute to a lack of regeneration and to arrest of alveolar growth in infants with bronchopulmonary dysplasia.